Intensity and Duration of Nitrogen Addition Jointly Alter Soil Nutrient Availability in a Temperate Grassland. Issue 3 (4th March 2022) - Niu, Guoxiang; Wang, Yinliu; Wang, Ruzhen; Ning, Qiushi; Guan, Huiling; Yang, Junjie; Lu, Xiankai; Han, Xingguo; Huang, Jianhui
Abstract: Increasing N input can alter soil nutrient availability and influence plant growth. Previous studies focused on N addition effects on N and P availability, while less on other mineral nutrients. Besides, how N addition duration affects nutrient availability has remained unclear. Based on a simulative N deposition experiment in a typical steppe with four N addition levels (0, 2, 10, and 50 g m −2 yr −1 ) under three N addition duration (2, 5, and 10 years), we determined contents of 10 mineral nutrients in surface soils. In the 0–10 cm soil, short‐term N addition (2‐year) significantly increased exchangeable Ca (+7.2%) and decreased exchangeable Mg (−22.5%) as compared with the control, while decreased available Fe, Cu, and Zn, but increased Mn remarkably (+80.4%). Medium‐term N addition (5‐year) significantly raised soil total N and available Fe, Mn and Cu, while decreased total P and exchangeable Ca, Na and Mg. The response patterns of these nutrients were largely similar in the 10–20 cm soil, but were weaker and significant only at high N inputs (50 g m −2 yr −1 ). Long‐term N addition (10‐year) significantly decreased contents of total base cations (K, Ca, Na, Mg) and micronutrients (Fe, Mn, Cu, Zn) by an average of 32.1% and 20.4%, respectively, across the two soil depths. Influences of pH and plant growth on micronutrients showed remarkable differences among different duration of N addition. These findings indicate that intensity and duration of N addition jointly alter soil nutrient availability and this should be considered in soil nutrient‐cycling modeling. Plain Language Summary: Multiple soil mineral nutrients support plant growth and help plants to complete their life cycles, but human activities have perturbed global N cycle, which may cause imbalance in the availability of different soil nutrients in ecosystems. In this report we thoroughly assessed the dynamics of essential mineral nutrients for plant growth under different rates and duration of N addition. Short‐term N addition (by 2 years) increased availability of Ca and Mn, but decreased the availability of Mg, Fe, Cu, and Zn. Longer‐term N addition (by 5 or 10 years) raised soil total N and the availability of Fe, Mn, and Cu, while decreased soil total P and the availability of Ca, Na, and Mg. Changes in soil pH and plant production after N addition were the main reasons to cause abovementioned changes in the availability of those mineral nutrients. These results revealed the existence of accumulative effects of N addition. Key Points: Both the rate and duration of N addition impact soil mineral nutrient contents Short‐term N addition induced different responses in micronutrients, while longer‐term treatments decreased total mineral nutrients Plant uptake impacted soil available micronutrients at early stage, while soil pH showed stronger effects at later stages